The Effect of Satisfaction on Public Services, Trust in Government and Perception of Corruption on Tax Awareness through Tax Morals - Sihar Tambun; Ani Haryati (Integrated Journal of Business and Economics (IJBE), 2022)
AbstractThe purpose of this study was to examine the direct effect of public service satisfaction, trust in the government and perceptions of corruption on tax morale, the direct effect of tax morale on tax awareness. As well as testing the effect of the three independent variables on tax awareness through tax morale. The research method used is quantitative with data collection techniques throughquestionnaire, method in taking samples using the hair method, namely the number respondent 5 – 10 times the number of indicators. AmountsampleThe results obtained are as many as 180 respondents as Taxpayer status. The sample was tested for validity and reliability testing as well as hypothesis testing through the SmartPLS software application. The results of hypothesis testing prove that there is a significant direct effect on trust in the Government and perceptions of corruption on tax awareness and a significant indirect effect on trust in the Government and perceptions of corruption on taxpayer compliance through tax awareness. However, there is no significant direct effect on public service satisfaction on tax awareness and no indirect effect on public service satisfaction on taxpayer compliance through tax awareness. From this research it can be concluded that when the government will increase tax morale, the first strategy that must be improved is trust in the Government, then the second is the perception of corruption. And to increase tax awareness through tax morale, what needs to be improved is firstly trust in the government and secondly perceptions of corruption.